Hukum Pengawasan Executive: Praktik Evaluasi dan Klarifikasi Terhadap Peraturan Desa Di Kabupaten Kubu Raya - Saliro, Sri Sudono; Subiyatno, Subiyatno (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2025)
The implementation of executive preview and executive review oversight mechanisms is very important, because both processes have the potential to improve the quality, consistency, and relevance of village legal products. This study aims to answer the main question of whether the local government supervises village regulations that are being drafted and those that have been enacted? Based on this main question, the researcher focuses on 2 sub-questions: First, how is the implementation of executive preview and executive review of village regulations in Kubu Raya Regency, second, what are the obstacles and supporting factors that influence the implementation of executive preview and executive review. The method used in this study is a qualitative method with an empirical legal approach. To obtain data, researchers conducted unstructured interviews with the Community and Village Empowerment Office of Kubu Raya Regency. Furthermore, the data obtained were analyzed with 3 steps: data reduction, data presentation and drawing conclusions and verification. The results of the study revealed that the implementation of executive preview and executive review of village regulations in Kubu Raya Regency refers to Permendagri 111/2014 and has been running in accordance with the Permendagri. The availability of village regulation draft formats/templates is a supporting factor for the smooth monitoring, evaluation, and clarification of these village legal products. However, the legal status of Kubu Raya Regional Regulation 4/2013 is one of the legal obstacles that must be resolved, in addition to the absence of a Regent's Regulation regarding the procedures for drafting regulations in villages as mandated by Article 32 of Home Affairs Ministerial Regulation 111/2014.